View of Islamic Law on The Maintenance of Children Against Parents - Muhammad Randy Hasibuan (International Asia Of Law and Money Laundering (IAML), 2022)
Humans who live in the world cannot be separated from the needs posed to survive and carry out their lives. The needs include: food, clothing and so forth. This need is called a living which means spending to preserve life and meet the needs and needs that apply according to situations and conditions. In Islam, the issue of maintenance is obligatory for certain reasons such as the husband's maintenance of his wife (due to marital factors), the parents ' maintenance of their children (kinship factors) and so forth. A good family, the father as the head of the family is obliged to provide maintenance to his child as well as the child is obliged to provide maintenance to both parents based on certain causes and circumstances,because between parents and children have a very close relationship and complement each other culturally. The obligation of giving maintenance by a child to his parents is also inseparable from the existence of a hadith called tamlik Hadith.